Wide Differences in Mode of Delivery Within Europe: Risk-stratified Analyses of Aggregated Routine Data from the Euro-Peristat Study. Issue 1 (March 2017) - Macfarlane, A.J.; Blondel, B.; Mohangoo, A.D.; Cuttini, M.; Nijhuis, J.; Novak, Z.; Ólafsdóttir, H.S.; Zeitlin, J.
Abstract : ( BJOG. 2016;123:559–568) Cesarean section rates have been on the rise in many developed countries over the past few decades. Cesarean section is a necessity in some high-risk conditions like placenta previa or fetal distress. Performance of the surgery is often governed by factors like parity, previous cesarean section, fetal presentation and multiplicity. The objectives of this study were two-fold: first to use aggregated population-based data from routine sources to review and understand the differences between obstetric intervention rates for European countries, and second to analyze the extent to which clinicians were likely to intervene in high-risk situations in countries with high overall cesarean rates.